European Norms Trap? EU Connectivity Policies and the Case of the Global Gateway - Karjalainen Tyyne (Springer, 2025)
Data cables, ports, and mobility are a rising theme in geopolitical competition, and the European Union (EU) also aims to develop a cutting-edge product for the fund-deficit connectivity market. Incapable of competing with China’s Belt and Road Initiative (BRI) in the quantity of investments, the EU’s 1-year-old connectivity initiative Global Gateway aims to challenge it with quality, providing more democratic, secure, equal, green, transparent, and sustainable alternatives to lower-income partners. While the BRI has been accused of creating debt traps in the same context, this article analyzes whether there is a risk of the EU’s norm-diffusing policy also having an undermining effect on partners’ agency. Based on a systematic analysis of EU policy documents and strategic communications, the article identifies three categories for the EU’s norms promotion: firstly, the support for regionalism, secondly, the prescribing of standards of connections, and thirdly, the defining of values to be applied in connectivity projects. The article argues that the EU communications reserve a limited role for the partners to participate in or to have control over the processes where values, norms, and standards of connectivity are created. The approach, unlikely to serve the EU’s declared goal of equal partnerships, is rather found to respond to the competitive international context.